Diagnostic Challenge of Sarcomatoid Variant of ALK-Positive Anaplastic Large Cell Lymphoma: Case Report and Updated Systematic Literature Review. (September 2021) - Song, Fuqin; Yu, Shili; Jia, Meng; Gao, Hongwen; Sun, Ping-Li
The sarcomatoid variant of anaplastic large cell lymphoma is an extremely rare histologic pattern of anaplastic large cell lymphoma that consists of spindle-shaped neoplastic cells and is easily misdiagnosed as a soft tissue sarcoma. We report a case of the sarcomatoid variant of anaplastic large cell lymphoma that was initially diagnosed as an inflammatory myofibroblastic tumor in our hospital and as liposarcoma after consultation. This article analyzed the features of this entity by reviewing the literature. Only 15 cases have been reported, most of which were misdiagnosed as sarcoma, sarcomatoid carcinoma, or inflammatory myofibroblastic tumor. Most of the reported cases showed a myxoid stroma, with a variable number of inflammatory cells. The hallmark cells usually can be found by careful evaluation of the slides. Immunohistochemistry including CD30, EMA, and ALK are the most useful for diagnosis. Most are III or IV stage, and have a good prognosis after chemotherapy.